2014
DOI: 10.3390/ijms15011201
|View full text |Cite
|
Sign up to set email alerts
|

Hispolon Decreases Melanin Production and Induces Apoptosis in Melanoma Cells through the Downregulation of Tyrosinase and Microphthalmia-Associated Transcription Factor (MITF) Expressions and the Activation of Caspase-3, -8 and -9

Abstract: Hispolon is one of the most important functional compounds that forms Phellinus linteus (Berkeley & Curtis) Teng. Hispolon has antioxidant, anti-inflammatory, antiproliferative and anticancer effects. In this study, we analyzed the functions of hispolon on melanogenesis and apoptosis in B16-F10 melanoma cells. The results demonstrated that hispolon is not an enzymatic inhibitor for tyrosinase; rather, it represses the expression of tyrosinase and the microphthalmia-associated transcription factor (MITF) to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…In addition to an antimetastatic ability via inhibiting the proteolytic activity of ECM proteinases, several studies have reported that hispolon exhibits antitumor ability by inducing cell cycle arrest and apoptosis, such as in melanoma, leukemia, hepatocellular cancer, and gastric cancer (Chen et al, ; Huang et al, ; Chen et al, ; Hsiao et al, ; Chen et al, ). Similarly, in NPC, Hsieh et al, demonstrated that hispolon induced phosphorylation of ERK1/2, JNK1/2, and p38 MAPK pathways, stimulating activation of caspase‐3, ‐8, and ‐9, which eventually induced the apoptosis of HONE‐1 and NPC‐39 cells (Hsieh et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to an antimetastatic ability via inhibiting the proteolytic activity of ECM proteinases, several studies have reported that hispolon exhibits antitumor ability by inducing cell cycle arrest and apoptosis, such as in melanoma, leukemia, hepatocellular cancer, and gastric cancer (Chen et al, ; Huang et al, ; Chen et al, ; Hsiao et al, ; Chen et al, ). Similarly, in NPC, Hsieh et al, demonstrated that hispolon induced phosphorylation of ERK1/2, JNK1/2, and p38 MAPK pathways, stimulating activation of caspase‐3, ‐8, and ‐9, which eventually induced the apoptosis of HONE‐1 and NPC‐39 cells (Hsieh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the antitumor effects of this phenolic compound have been demonstrated in the cell lines of various cancers. In addition, several studies have shown that hispolon can induce cell cycle arrest and apoptosis in cancer cells including melanoma, leukemia, hepatocellular cancer, and gastric cancer (Chen et al, , Huang et al, ; Chen et al, ; Hsiao et al, ; Chen et al, ). Furthermore, hispolon has also been shown to inhibit metastasis of hepatoma cells by reducing the expression of MMP‐2, MMP‐9, and uPA through suppression of the PI3K–Akt and ERK signaling pathways (Huang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The total amount of melanin in each cell suspension was determined by recording the absorbance at 405 nm [13].…”
Section: Melanin Content Analysismentioning
confidence: 99%
“…The cell-based melanin content assay in mouse melanocytes (e.g., B16F10 mouse melanoma cells) is better than the mushroom tyrosinase activity assay because it provides more credible results http://dx.doi.org/10.1016/j.enzmictec.2014.09.008 0141-0229/© 2014 Elsevier Inc. All rights reserved. [13,14]. However, this assay is time-consuming, requiring approximately 3-5 days to complete.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, HPL has demonstrated antitumor effects in various types of cancer cells, including melanoma, leukemia, hepatocarcinoma, bladder cancer and gastric cancer cells (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%